Analisis Pengaruh Tingkat Inflasi, Pendapatan Pegadaian dan Harga Emas terhadap Penyaluran Kredit KREASI PT. Pegadaian Cabang Kupang : Periode 2016-2023 (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze the effect of inflation rate, pawnshop income and gold price on the distribution of KREASI credit of PT. Pegadaian Kupang (Period 2016-2023). The type of research used is a case study method with a quantitative approach. This study uses secondary data in the form of inflation rate data, pawnshop income, gold price, and distribution of KREASI credit in the period from the first quarter of 2016 to the fourth quarter of 2023 in PT. Pegadaian Kupang. The data analysis technique used is multiple linear regression analysis, classical assumption test, and hypothesis test with the help of SPSS software. The results of the study indicate that simultaneously the inflation rate, pawnshop income and gold price have a positive effect on the distribution of KREASI credit. The inflation rate and income partially have a negative effect on the distribution of KREASI credit. The price of gold partially has a positive effect on the distribution of KREASI credit